Intravascular Papillary Endothelial Hyperplasia (Masson's Tumor) of the Mouth - A Case Report - Ronell Bologna-Molina; Guillermo Amezcua-Rosas; Israel Guardado-Luevanos; Patricia Lorelei Mendoza-Roaf; Tomás González-Montemayor; Nelly Molina-Frechero (Karger Publishers, 2010)
We report a rare case of intravascular papillary endothelial hyperplasia (IPEH) of the oral mucosa. This neoplasm, known as Masson's tumor, is an unusual vascular lesion of proliferating endothelial cells. It is usually confined to the lumen of preexisting vessels or vascular malformations. The principal significance of IPEH is its microscopic resemblance to angiosarcoma and possible misdiagnosis as such. Achieving a correct diagnosis is essential to avoid subjecting a patient to unnecessarily aggressive therapy. For this reason, awareness of this lesion is very important for dermatologists and dentists. In this article, we discuss the clinical features, histopathological characteristics, and management of IPEH and review the pertinent literature.